A new P2-type layered oxide cathode with superior full-cell performances for K-ion batteries. Issue 37 (6th September 2019) - Hwang, Jang-Yeon; Kim, Jongsoon; Yu, Tae-Yeon; Jung, Hun-Gi; Kim, JaeKook; Kim, Kwang-Ho; Sun, Yang-Kook
Abstract : The P2-type K0.75 [Fe0.1 Ni0.1 Mn0.8 ]O2 cathode synthesized via an electrochemical ion exchange method has a highly stable layered oxide framework, demonstrating its outstanding power capability as well as long-term cycling stability. Abstract : K-ion batteries (KIB) have attracted considerable attention as a potential alternative to Li-ion batteries because of their low cost and high energy density. However, their development and durability have been severely limited by the lack of suitable cathodes with high capacity and good cycle life. Here, we prepare a low-cost Mn-based layered oxide, P2-type K0.75 [Mn0.8 Ni0.1 Fe0.1 ]O2 (P2-K0.75 MNFO2 ), via an electrochemical ion-exchange process and demonstrate its excellent K storage performance as a cathode for KIBs. During the charge–discharge process, P2-K0.75 MNFO2 can release and store considerable amounts (∼0.5 mol) of K + ions without multiple phase transitions in the voltage range of 1.5–3.9 V ( vs. K/K + ), as verified by X-ray diffraction characterization and first-principles calculations. Owing to its highly stable layered oxide framework, P2-K0.75 MNFO2 delivers a high reversible capacity of 110 mA h g −1 at 0.1C and exhibits an outstanding cycle retention of 70% over 200 cycles at both 1C and 10C. In addition, a full cell with P2-K0.75 MNFO2 as the cathode and hard carbon as the anode demonstrates long-term cycling stability over 1000 cycles, illustrating the feasibility of a safe and practical KIB system.